Knowledge, Risk Preference And Investment Return On Student Investing Interest In The Islamic Capital Market - Selamat Muliadi; Willson Gustiawan; Hakim Hakim; Saiful Bahri; Alfiana Alfiana (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2023)
This research aims to analyze and show the effect of investment knowledge, risk preferences, and investment returns on student investment interest. This research uses quantitative methods with regression analysis. The research population was 3,710 students of the Faculty of Islamic Economics and Business, State Islamic University of Mataram. The sampling technique uses accidental sampling. The sample size was calculated using the Slovin approach to obtain a sample of 98 respondents. The data source comes from primary data in questionnaires and secondary data from the literature. Data analysis was carried out with several tests, including validity tests, reliability tests, classic assumption tests, multiple linear regression analysis, and coefficient of determination tests using IBM SPSS version 21 software. The results of this study indicate that investment knowledge and returns positively and significantly affect student investment interest. Risk preference does not influence student investment interest. These findings can be used as a reference for policymaking for the Indonesia Stock Exchange (IDX) in increasing the number of investors targeting the millennial generation.